Transformation Of Soul Education In The Digital Era: A Synthesis Of Al-Ghazali And Ibn Qayyim Al-Jawziyyah’s Thought - Muhammad Ghufron; Rifqi Khairul Anam; Khoiriyah Khoiriyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to formulate a framework of Tazkiyah-Based Digital Resilience through a hermeneutical synthesis of the educational thoughts of Al-Ghazali and Ibn Qayyim al-Jawziyyah in response to the moral and psychological crises faced by students in the digital era. Using a qualitative library research design grounded in Hans-Georg Gadamer’s philosophical hermeneutics, this research applies the concept of fusion of horizons to integrate classical Islamic texts with contemporary digital challenges such as doomscrolling, algorithmic addiction, and ethical disorientation on social media. The findings reveal that Al-Ghazali provides an epistemological foundation by positioning the qalb (heart) as the center of moral consciousness and knowledge discernment, while Ibn Qayyim contributes a transformative methodological framework through the stages of maqāmāt and practices of mujāhadah. The synthesis of both perspectives results in an applicative pedagogical model in which mujāhadah is reinterpreted as digital self-discipline, muraqabah as digital integrity, and muhāsabah as reflective information auditing. This framework offers a conceptual contribution to Islamic Religious Education by shifting moral education from external regulation toward internalized spiritual resilience, enabling students to navigate digital environments with ethical awareness, self-control, and spiritual maturity.